Workload and Sleep Quality Among Medical Surgical Ward Nurses in a Private Hospital in Eastern Indonesia - Neni Ekaristi Sianturi; Nora Berliana Permatasari Gulo; Petronela Apriliani D Kelen; Janwar Olang (Faculty of Nursing, Universitas Pelita Harapan, 2026)
Background: Nurses in medical-surgical wards manage high patient loads, complex clinical conditions, administrative duties, and extended working hours. These demands may increase physical and psychological strain, potentially impairing sleep quality and affecting performance and patient safety. This study aimed to examine the relationship between workload and sleep quality among nurses in a private hospital in Eastern Indonesia. Methods: A quantitative cross-sectional design was applied. All 96 nurses working in the medical-surgical ward were included using total sampling. Data were collected through structured questionnaires measuring workload and sleep quality. Descriptive analysis was used to summarize respondent characteristics, while the chi-square test was performed to determine the association between workload and sleep quality. Results: There was a statistically significant relationship between workload and nurses’ sleep quality (p = 0.006). A total of 57.3% of nurses experienced a heavy workload, while 34.4% had a light workload. Furthermore, 91.7% of nurses reported poor sleep quality, and only 8.3% reported good sleep quality. Conclusion: Higher workload is significantly associated with poorer sleep quality among nurses. Hospitals are encouraged to routinely evaluate workload and implement preventive strategies to promote nurses’ well-being and maintain quality of care.